Variabel Yang Mempengaruhi Nilai Perusahaan Pada Masa Pandemi Covid-19 - Santoso, Madeline; Yanti, Yanti (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The objectives of this research are to investigate the effect of capital structure, profitability, cash holding, and firm size on the firm value of basic materials companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2021. The technique that was used in this research is purpose sampling with the results about 17 basic material companies listed on IDX. In this research, multiple linear regression was tested using software called SPSS IBM Statistics. The result of this study stated that firm size has a significant and positive effect on firm value, on the other hand capital structure, profitability, and cash holding have no significant effect on firm value. The result of different tests before and during the COVID-19 pandemic stated that there was no difference in the average of firm value.